Legal Protection of Abandoned Land in Indonesia from the Perspective of Maqasid al-Shari'ah - Dodek Prajuliara; Tetty Marlina Tarigan (Hakamain: Journal of Sharia and Law Studies, 2025)
Land has a strategic role in national development from economic, social, and welfare perspectives. However, many lands in Indonesia remain categorized as abandoned because they are not utilized according to the purpose of granting land rights, which creates legal uncertainty and undermines the social function of land. This study aims to analyze the legal protection of abandoned land after the enactment of Government Regulation Number 20 of 2021 concerning the Management of Abandoned Areas and Land and to examine it from the perspective of Maqasid al-Shariah. The research employs a qualitative field research approach conducted in several locations where abandoned land cases have been identified. Data were collected between May and July 2025 through semi-structured interviews, direct observation, and document analysis involving 15 informants consisting of land office officials, village authorities, Islamic law scholars, and community members. The findings indicate that the legal protection of abandoned land can be implemented through preventive and repressive mechanisms, including regulatory supervision, monitoring of land utilization, and dispute resolution processes. From the perspective of Maqasid al-Shariah, the policy of controlling abandoned land aligns with the principles of hifz al-mal (protection of property) and maslahah (public welfare), as it encourages productive land use and equitable resource distribution. This study concludes that the implementation of Government Regulation No. 20 of 2021 strengthens legal certainty and supports social justice in land governance. Academically, this research contributes to integrating agrarian law analysis with the normative framework of Maqasid al-Shariah in evaluating land management policies in Indonesia.